Strategi penanganan Covid-19 melalui pemberdayaan UMKM dalam memproduksi APD di Kota Pekanbaru - Iwantono Iwantono; Genny Gustina Sari; Yohannes Firzal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Since March 2020 the spread of the Corona virus has hit almost all parts of the world. The number of victims is increasing while a cure has not yet been found. The angry community then began to take the initiative to save themselves and their families by buying medical devices such as masks, handsanitizers to APD (Personal Protective Equipment) clothes or better known as Hazmat shirts. Unfortunately, the price of these three materials has increased many times over, naughty parties play by piling up goods and then throwing them into the market at an unreasonable price. Do not lose their mind, people rack their brains to take advantage of new business opportunities in the Covid-19 era, including making and mixing their own handsanitizers, sewing masks and of course hazmat suits. The scarcity of these items actually affects the performance of medical personnel. This dedication is made in order to help empower UMKM in Pekanbaru City to try to read the market and produce their hazmat suits themselves. As a result, with the intense competition and the lack of public interest in sewing Hazmat clothes, the service team managed to embrace UMKM that manage their own convection, even though they are on a small scale.